Sport Mall Di Pekanbaru Berdasarkan Pendekatan Arsitektur High-Tech - Ghina Revita Sakinah; Yohannes Firzal; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The rise of mall construction in the city of Pekanbaru today makes up the new idea about sports facilities by combining shopping places in it. Sports Mall is accommodate of two functions between places supporting sports activities and a place to support the city's economic activities as well as an icon of city development that has not existed before. The Sports Mall character that space efficiency, building support structures and aesthetics as an expression of sports and displays an open impression that is able to connect public space inside and outside the building. To fulfill this character, it can be done with the approach of the principles of high-tech architecture. So the design of Sports Mall prioritizes the structure and technology in the building that is in harmony with the character of the building inside.Keywords: Sport, Sports Mall, Structures, High-tech Architecture